Sex Determination Using Mastoid Process Measurements in Brazilian Skulls - Galdames, Ivan Claudio Suazo [UNIFESP] (2008)
The mastoid process characteristics are of great utility in the diagnosis of sex. De Paiva & Segre (2003) described that sex diagnosis was possible based on the determination of the area of the triangle formed by the points porion, mastoidale, and asterion. The purpose of this study was to determine the existence of sexual dimorphism in the dimensions and the area of the mastoid triangle using statistical and discriminant function analysis. A total of 81 skulls of Brazilian individuals that were part of the Museum of the Federal University of Sao Paulo (UNIFESP) collection were used, with sex and ages known: 50 men and 31 women between 40 and 70 years of age (mean 51.58 years, SD 7.319). Most of the lineal dimensions and the calculated areas were higher in men than in women. Only the distance porion-mastoidale, the area of the right mastoid triangle and the total area, was higher and more significant in men with p < 0.01. The analysis of the discriminant function showed that the group of analyzed lineal dimensions presents a low discriminant capacity (Lambda of Wilks = 0.960, Canonical Correlation = 0.199); only porion-mastoidale allowed one to distinguish men's groups from women with a general accuracy of 64.2%, but with a high sensibility to classify men (93%) and a very low sensibility for women (17.7%). These results indicate that the determination of sex based on the dimensions of the mastoid triangle leads to underestimate the women, hence being of less utility in practice.